CZY ZALEWA NAS FALA PRZEMOCY? POLITYCY I MEDIA VS. DANE STATYSTYCZNE - Hamer, Katarzyna; Hamet, Hanna (Civitas et Lex, 2014)
By detailed analyses of Polish and world statistics, the authors search for the answer if in fact, as some politicians and citizens claim, the world and in particular European Union and Poland are overcome by the wave of violence. Data gathered, among others, by Polish Public Opinion Research Center (CBOS), Eurostat and United Nations Office on Drugs and Crime (UNOCD), as well as anthropologists and police, clearly prove the opposite. Scientific comparisons concerning violence over the centuries show that its scale drastically decreased and the world gets safer with time. Statistical reports of the United Nations especially clearly indicate European Union (including Poland) as particularly peaceful region against the rest of the world, having the lowest murder rates. Eurostat data confirm these results, also showing decrease in other crimes over the years. Polish police data similarly prove existence of this trend and CBOS indicates that it is reflected in increasing sense of security among Poles. In the second part of the article the authors explain potential reasons for using such false slogans as “increasing wave of violence” by politicians and raising fear in voters as well as psychological mechanisms responsible for their potential effectiveness.